2021
DOI: 10.1371/journal.pone.0253206
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of cohort studies: Traumatic brain injury and risk of Alzheimer’s Disease

Abstract: Introduction Recently, some epidemiological studies have reported that cognitive disorders in elderly people is accelerated with traumatic brain injury. But the causal relationship between traumatic brain injury and AD is still an area of controversy. Aims Our review was conducted to estimate the relation between traumatic brain injury and risk of AD. Methods All longitudinal population-based studies comparing incidence of AD between subjects with and without traumatic brain injury from their inception to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…The mechanisms underlying this risk are unclear and no clear link has notably been evidenced with heading the ball 28 . However, prolonged and repetitive exposure to traumatic head impacts from collisions and the ball might alter intracranial hypertension causing diffuse amyloid plaques and augmenting the risk of developing Alzheimer's disease 29 . Confirmation via prospective studies is necessary while research registering former footballers for brain donation autopsy at their time of death would be useful to inform on the existence of neurodegenerative pathologies especially as it is currently weak to non‐existent evidence for the link between football participation and long‐term neurological or cognitive deficits 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying this risk are unclear and no clear link has notably been evidenced with heading the ball 28 . However, prolonged and repetitive exposure to traumatic head impacts from collisions and the ball might alter intracranial hypertension causing diffuse amyloid plaques and augmenting the risk of developing Alzheimer's disease 29 . Confirmation via prospective studies is necessary while research registering former footballers for brain donation autopsy at their time of death would be useful to inform on the existence of neurodegenerative pathologies especially as it is currently weak to non‐existent evidence for the link between football participation and long‐term neurological or cognitive deficits 8 .…”
Section: Discussionmentioning
confidence: 99%
“…28 However, prolonged and repetitive exposure to traumatic head impacts from collisions and the ball might alter intracranial hypertension causing diffuse amyloid plaques and augmenting the risk of developing Alzheimer's disease. 29 Confirmation via prospective studies is necessary while research registering former footballers for brain donation autopsy at their time of death would be useful to inform on the existence of neurodegenerative pathologies especially as it is currently weak to non-existent evidence for the link between football participation and long-term neurological or cognitive deficits. 8 Arguably, it is also important to continue the present research as it is possible that certain risk factors potentially associated in the past with the development of neurodegenerative disease might no longer exist or will, to a lesser extent, influence the future risk.…”
Section: Mortality Due To Neurodegenerative Diseasesmentioning
confidence: 99%
“…In this context, our findings suggest that there is substantial overlap between the brain's spatial patterns of vulnerability to (A) AD-related cortical thinning, (B) AD-related white matter demyelination, and (C) mTBI-related intracortical demyelination. Thus, because mTBI increases the risk of AD and related dementias ( 47 , 48 ) through uncertain mechanisms, further study on how post-traumatic demyelination patterns can translate into higher AD risk is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear on why early TBI experience increases the chance of dementia and neurodegeneration in later life. A recent meta-analysis showed that TBI increases the rate of AD about 1.5 times [ 47 ]. A study from military veterans shows that TBI increases the risk of having Parkinson’s disease by approximately 56% [ 48 ].…”
Section: Discussionmentioning
confidence: 99%